Правовые проблемы международной защиты культурных ценностей в случае вооруженного конфликта (Обязательства Республики Польша) - Gerecka-Żołyńska, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the legal issues related to the obligations of the Republic of Poland in the context of an armed conflict according to the legal aspects of an international protection of cultural property.